Effect of plasma-activated water and antioxidant packaging on the degradation kinetic of minimally processed fennel quality during storage - Syed Mudabbar Hussain Shah; Stefania Volpe; Francesca Colonna; Vincenzo Valentino; Francesca De Filippis; Maria del Carmen Razola-Diaz; Vito Verardo; Silvana Cavella; Elena Torrieri (Applied Food Research)
This study investigated the impact of an alternative washing technology, plasma-activated water (PAW), in combination with antioxidant packaging, on the physicochemical, nutritional, and microbiological properties of minimally processed fennel (MPF) stored for maximum 21 days at three temperatures (4 °C, 8 °C, 12 °C). A kinetic approach was applied to describe the quality changes of MPF over time, and the Arrhenius model was used to predict the effect of temperature on kinetic constants. The pseudo-zero-order kinetic model adequately explained the total colour change and total polyphenol content over time. In contrast, the pseudo-first-order kinetic model described the changes in antioxidant capacity and ascorbic acid. The nutritional properties of MPF were effectively preserved thanks to the combined treatments when the product is stored at 4 °C. However, the physical properties were not affected. Microbiological analysis showed that combined treatments could slow the growth of yeasts, mould, and Enterobacteriaceae during the storage at 4 °C and 8 °C. In conclusion, the results suggested that the combination of PAW and antioxidant packaging could effectively be used as a potential application for preserving the nutritional quality of MPF, particularly when stored at lower temperatures, such as 4 °C.